A Comprehensive Review on Efficacy and Adverse Events Associated With Different Covid-19 Vaccines‎ - Borra, Swathi Swaroopa; C K, Narenthiran; Kumar, Dinesh; M, Ayilya; G. K, Sadagoban (Jordan Journal of Pharmaceutical Sciences, 2022)
To combat COVID-19, various health agencies around the world gave emergency approval for vaccines. Therefore, the long-term protective effect and the potential adverse effects of the vaccines on immunocompromised patients, pregnant women and geriatrics might not be well-established. The aim of this review was to assess the safety and efficacy of a number of the most commonly approved vaccines all over the world. A review was made to identify clinical trials that studied the vaccines’ efficacy and case reports of potential suspected vaccine-related adverse events. The electronic databases searched to identify relevant studies were Science Direct, PubMed/Medline, Scopus and MedRxiv. Seven randomized controlled trials which assessed the efficacy of COVID-19 vaccines and case reports which reported the vaccines’ adverse events were included in the review. The efficacy of the vaccines was found to be 94.6% for Pfizer vaccine, 94.1% for Moderna vaccine, 66.1% for Johnson and Johnson’s, 76.4% for Covishield, 91.6% for Sputnik, and 77.8% for Covaxin. No severe adverse events were reported in the studies. All the reported adverse events were mild, self-sustaining and did not require any medical intervention. All the COVID-19 vaccines demonstrated promising immunogenicity profile, different degrees of protective effectiveness and a tolerable safety profile. However, further research to evaluate the efficacy and safety in vulnerable populations including immunocompromised patients, pregnant women and geriatric populations are needed. The long term post marketing surveillance becomes a very important part of identifying the efficacy and side effects among different populations.